Influence of Financial Performance and Environmental Performance on Company Reputation - Oktavianus, Laurentius Christian; Daromes, Fransiskus E; Asri, Marselinus (AJAR, 2024)
The purpose of this research is to analyze the reciprocal influence between financial performance and environmental performance on corporate reputation. The population used consists of non-financial companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2022. The sample size is 28 companies each year, selected using purposive sampling. This study utilizes documentary data, including annual reports, the Corporate Image Index (CII) published by Frontier Consulting Group, and the PROPER index published by the Ministry of Environment and Forestry.The results of this research, using simple linear regression analysis, indicate that financial performance has a positive and significant effect on corporate reputation. Corporate reputation has a positive and significant effect on financial performance. Environmental performance has a negative and non-significant effect on corporate reputation, while corporate reputation has a negative and significant effect on environmental performance. Environmental performance has a negative and significant effect on financial performance, and financial performance has a negative and significant effect on environmental performance.The implications of this research, especially for companies, are that it can serve as a basis for strategic decisionmaking. On the other hand, performance is a key aspect in developing reputation for the future.